THE EFFECT OF USING BIG BOOK MEDIA BASED ON PEER TUTORS TO STUDENTS’ COGNITIVE ABILITY OF MADRASAH IBTIDAIYAH - Sulaiman, Umar; Djafar, Hamsiah; Mihrani, Mihrani; Mundzir, Chaerul (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
This research describes the effect of using Big Book media based on peer tutors to cognitive abilities in the fifth-grade students at MIN 1 Makassar. This research used quantitative methods with a pre-experimental design one-shot case study. The sample of this study was 57 fifth-grade students. The results of this research have been obtained. First, the use of Big Book media based on peer tutors in the fifth-grade students of MIN 1 Makassar was in the good category with an average value in the interval 113-118. Second, the cognitive abilities were fairly high at intervals of 66-76. Third, the hypothesis test results using one sample t-test analysis indicated the effect of using Big Book media based on peer tutors on the students’ cognitive abilities. Therefore, this study is expected to be a consideration for schools and teachers to use Big Book media to accommodate students’ learning needs. Abstrak: Penelitian ini menjelaskan pengaruh penggunaan media Big Book berbasis tutor sebaya terhadap kemampuan kognitif siswa kelas V di MIN 1 Makassar. Penelitian ini menggunakan metode kuantitatif dengan desain pre-experimental one-shot case study. Sampel penelitian ini sevanyak 57 siswa kelas V. Hasil penelitian yang telah diperoleh, pertama, penggunaan media Big Book berdasarkan tutor sebaya pada siswa kelas V MIN 1 Makassar berada pada kategori baik dengan nilai rata-rata pada interval 113-118. Kedua, kemampuan kognitif cukup tinggi dengan interval 66-76. Ketiga, hasil uji hipotesis dengan menggunakan analisis one sample t-test menunjukkan adanya pengaruh penggunaan media Big Book berbasis tutor sebaya terhadap kemampuan kognitif siswa. Oleh karena itu, penelitian ini diharapkan dapat menjadi bahan pertimbangan bagi sekolah dan guru untuk menggunakan media Big Book yang mampu mengakomodasi kebutuhan belajar peserta didik.